HUKUM ISLAM DAN MULTIKULTURALIS- PLURALITAS DI INDONESIA - Hannani Hannani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
Culture is a whole system of ideas, actions and products of human endeavor to fulfill their lives by learning, all of which are arrayed in people's lives. Pluralism is understood that a plurality of saw it as a reality that is positive and as a necessity for salvation of mankind. Multiculturalism is a recognition that some of the different cultures can exist in the same environment and benefit from each other. Or the recognition and promotion of cultural pluralism. Since the early development of Islam as a conception of reality has accepted socio-cultural accommodation. This accommodation is increasingly seen as an Islamic region evolved such that it became a worldwide religion. In certain cases, accommodation is created in such a way, giving rise to